Attenuator LRR – a regulatory tool for modulating gene expression in Gram‐positive bacteria. Issue 6 (15th March 2021) - Cai, Xia; Wang, Qian; Fang, Yu; Yao, Die; Zhan, Yunda; An, Baoju; Yan, Bing; Cai, Jun
Summary: With the rapid development of synthetic biology in recent years, particular attention has been paid to RNA devices, especially riboswitches, because of their significant and diverse regulatory roles in prokaryotic and eukaryotic cells. Due to the limited performance and context‐dependence of riboswitches, only a few of them (such as theophylline, tetracycline and ciprofloxacin riboswitches) have been utilized as regulatory tools in biotechnology. In the present study, we demonstrated that a ribosome‐dependent ribo‐regulator, LRR, discovered in our previous work, exhibits an attractive regulatory performance. Specifically, it offers a 60‐fold change in expression in the presence of retapamulin and a low level of leaky expression of about 1–2% without antibiotics. Moreover, LRR can be combined with different promoters and performs well in Bacillus thuringiensis, B. cereus, B. amyloliquefaciens, and B. subtilis . Additionally, LRR also functions in the Gram‐negative bacterium Escherichia coli . Furthermore, we demonstrate its ability to control melanin metabolism in B . thuringiensis BMB171. Our results show that LRR can be applied to regulate gene expression, construct genetic circuits and tune metabolic pathways, and has great potential for many applications in synthetic biology. Abstract : In the present study, we demonstrated that a ribosome‐dependent ribo‐regulator, LRR, discovered in our previous work, exhibits an attractive regulatory performance. We show its ability to control melanin metabolism in Bacillus thuringiensis BMB171.